2017
DOI: 10.5039/agraria.v12i1a5413
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional additives in high moisture corn silage

Abstract: Because of the high total digestible nutrient and dry matter (DM) digestibility contents , high moisture silage may be an alternative to maximize animal performance. Thus, the objective of this study was to evaluate the chemical composition, ruminal degradability and aerobic stability of high moisture corn silage (pure corn grain silage and soybean-, sunflower-or urea-enriched silages). Plastic barrels with capacity of 200 kg were used as experimental silos, which remained closed for nine months. The experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 12 publications
4
6
1
Order By: Relevance
“…The high moisture triticale silage with urea presented highest value for the soluble fraction (a) of the dry matter, corroborating with the findings of Calixto, Jobim, Osmari and Tres (2017). According to same authors, the addition of urea in high moisture silages increases the crude protein content, favoring the ruminal microbial development and improving the utilization of fibrous fraction.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…The high moisture triticale silage with urea presented highest value for the soluble fraction (a) of the dry matter, corroborating with the findings of Calixto, Jobim, Osmari and Tres (2017). According to same authors, the addition of urea in high moisture silages increases the crude protein content, favoring the ruminal microbial development and improving the utilization of fibrous fraction.…”
Section: Resultssupporting
confidence: 83%
“…Liu, Mckinnon, Thacker and Yu (2012) described effective degradability of 82.7%, assuming a rate of passage of 6% h -1 . The values of effective degradability of dry matter are superior to those described by Jobim et al (2008) and similar to those found by Calixto et al (2017) for high moisture corn, which demonstrates the nutritional potential for use of triticale grains for ruminants.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…However, its use must be strategic, depending on each case. Soybean grain with a 20% inclusion in the corn grain silage has shown positive results in terms of nutritional quality, fermentation in the silo, and animal response (Calixto, Jobim, Osmari, & Tres, 2017).…”
Section: Introductionmentioning
confidence: 99%